(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2008)
This study tries to inquire about the imperial evergetism in the towns of Roman Italy during the reigns of Trajan (98-117 A.D.) and Hadrian (117-138 A.D.). According to the epigraphical, archaeological and literary sources, it was possible to get an overview about the imperial involvements in Italy. The research has come to a temporary balance of the evergetism activities carried out by the two principes, pointing out the different reasons at the origin of their respective open-handedness. On the other hand it is pretty clear, as to Trajan’s and Hadrian’s building activity, a shared aim referable to the welfare and prosperity of Italian towns. At last, thanks to the consideration of some particular cases, it was possible to stress the ways of cooperation between emperors and local communities, allowing to understand more clearly the punctual process of development of a single act of evergetism.